Family foster care in Portugal : perceptions of child protection professionals - Mendonça, Maria Ana Teixeira Aranha Furtado de (2019)
Several years after changes were made to the Portuguese law that protects children and young people at risk, it seems little has been done to implement and prioritise Family Foster Care (FFC) in cases when children and young people need to be placed in out-ofhome care. In this regard, the main goal of this study is to understand the perceptions of professionals involved in the foster care system, concerning FFC placement. The Family Foster Care Perceptions Questionnaire – Version for Professionals, was filled out by 101 participants, between the ages of 20 to 58, from different professional backgrounds and child protection contexts. Main findings show that 69.3% of respondents seem to be familiar with FFC and about 50% consider it to be an adequate measure. Professionals also seem to value its child-centred approach and ability to promote child development and healthy attachment relationships, due to the benefits of a family environment. As barriers and as necessary conditions for placement success, respondents identified similar issues, mainly regarding regulations and procedures, relating to selection, evaluation, training, monitoring and support for foster families. Main conclusions emphasise the importance of professionals’ perceptions, as they inform about necessary changes to the child protection system.